2005
DOI: 10.1055/s-2004-830521
|View full text |Cite
|
Sign up to set email alerts
|

Improved Spinal Cord Perfusion during Thoracoabdominal Aortic Repair

Abstract: TcMEP loss is associated with spinal cord ischaemia, causing postoperative paraplegia. TcMEP monitoring is an excellent method to detect spinal cord ischaemia at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Interestingly, we observed no type-II endoleaks after complete overstenting of the LSA in our series. If type-II endoleaks occur, coil embolization or surgical ligation of the LSA may become necessary [14]. The rate of primary endoleaks after thoracic aortic ESI was reported to be 11-25% [2,7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we observed no type-II endoleaks after complete overstenting of the LSA in our series. If type-II endoleaks occur, coil embolization or surgical ligation of the LSA may become necessary [14]. The rate of primary endoleaks after thoracic aortic ESI was reported to be 11-25% [2,7,10].…”
Section: Discussionmentioning
confidence: 99%
“…Open surgical repair of the aortic arch, the descending and the thoracoabdominal aorta are invasive procedures with high morbidity and mortality rates [4,14]. ESI is a less invasive and effective treatment for high-risk patients showing a low complication rate [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiences during open surgical TAA treatment have shown that this procedure is followed by a quick recovery of evoked potentials, and consequently, has a positive effect on the neurological outcome of our patients [8,9]. Therefore, we conclude that an early adjustment of ICP below 15 mmHg proves to be sensible also during future complex TAAendoluminal treatment.…”
Section: Discussionmentioning
confidence: 62%
“…Three main factors contribute to spinal cord injury: ischemia during aortic cross-clamping, unsuccessful reattachment of spinal cord-perfusing arteries, and cytotoxic damage caused by hypotension and reperfusion injury [2]. On account of the experiences of former studies [3][4][5][6][7][8][9], neurophysiologically monitored open surgery of TAA has proven to be of positive neurological outcome. However, the open surgical technique is associated with the severe risk of paraplegia and mortality.…”
Section: Introductionmentioning
confidence: 98%
“…The most important challenge remains to identify a method consistently protecting the spinal cord from ischemic injury [5]. Neurophysiological monitoring, a method to observe spinal cord function during open aortic surgery and endovascular aortic repair (EVAR), is based on the analysis of transcranial motor-evoked potentials (tcMEP) and somatosensory-evoked potentials (SSEP) by electric stimulation of the motor cortex and the peripher-al nerves [6]. As this method is not yet established as standard in open aortic surgery or EVAR, there is an urgent need to identify potential problems associated with it and innovations to prevent them.…”
mentioning
confidence: 99%